Práxis dialógica de grupo : contribuições de Elli Benincá para a formação docente - Araújo, Daniela De David (2025)
Overcoming the dichotomy between theory and practice in teacher education was one of Elli Benincá’s (1936–2020) main investigative concerns as a professor and researcher in the field of Education. In his writings, he advocates a systematic process of investigating teaching practice through observation and reflection on one’s own performance, as a means of reframing pedagogical common sense. This process, however, requires the presence of a group in which teachers engage in dialogue - with themselves, their peers, theory, and context. The knowledge that emerges from praxis - linking thought and action - supports teachers in transforming their individual practice, which in turn feeds back into the group to which they belong. With this in mind, during his working time at the University of Passo Fundo, Benincá led initiatives and groups that promoted dialogical pedagogical relationships at various levels of education - fostering knowledge, autonomy, critical thinking, and personal and social transformation. This recognition, evidenced in testimonies and publications over different periods, leads to the central research question of this doctoral study: what pedagogical-formative dimension is revealed in Benincá’s group-based praxis in the process of teacher education? The aim is to analyze the pedagogical thought of educator Elli Benincá, identifying the principles that characterize praxis as he understood and practiced it. Dialogue is thus addressed as a central concept in connection with group processes, seeking to establish the relationship between dialogical praxis and the hermeneutic-formative approach. The theoretical framework is grounded primarily in the works of Gadamer (2009; 2012c), Paulo Freire (2020; 2023), Jean Grondin (2011; 2024), and Flickinger (2010; 2023; 2025). The writings of Benincá himself (2010a), particularly his book Educação: práxis e ressignificação pedagógica, also serve as a fundamental reference. Methodologically, this is a qualitative study, with a hermeneutic and interpretive approach supported by theoretical, bibliographic, and documentary review, and further grounded in empirical investigation. Based on Gatti (2002; 2005; 2012), oral interviews and questionnaires were used to reconstruct the experiences of Benincá as remembered by family members, former colleagues, and former participants of the research group linked to the project A relação teoria e prática no cotidiano dos professores. In alignment with the study’s objectives, hermeneutics is emphasized as an intellectual and investigative approach that involves reflective dialogue among the sources (texts and participants), the context, and the researcher, in the construction of meaning. To ensure coherence and cohesion, the research is structured into five additional chapters, beyond the Introduction and Final Considerations. The findings highlight the pedagogical-formative dimension of Benincá’s Praxis, linking it with the foundations of Gadamerian hermeneutic dialogue by interweaving: i) listening and reflective, interdisciplinary dialogue as an attitude for human formation; ii) observation, reading and writing, critical reflection, and group participation as methodological strategies; iii) the procedural, collaborative, and co-responsible work of group members as an ethical principle; and iv) self-education and social transformation as ongoing commitments. By creating and sustaining peer dialogue groups in teacher education, Benincá fostered continuous reflection on teaching practice, promoting intellectual development and challenging pedagogical common sense in favor of human emancipation. His leadership also embodied principles of collaboration, participation, and democracy, as a form of resistance to individualism. The study concludes with initial reflections on the contemporary relevance of Benincá’s Praxis in today’s educational context.